2021
DOI: 10.3389/fonc.2021.659251
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-seq Identification of the Cellular Molecular Characteristics of Sporadic Bilateral Clear Cell Renal Cell Carcinoma

Abstract: Bilateral renal cell carcinoma (RCC) is a rare disease that can be classified as either familial or sporadic. Studying the cellular molecular characteristics of sporadic bilateral RCC is important to provide guidance for clinical treatment. Cellular molecular characteristics can be expressed at the RNA level, especially at the single-cell degree. Single-cell RNA sequencing (scRNA-seq) was performed on bilateral clear cell RCC (ccRCC). A total of 3,575 and 3,568 high-quality single-cell transcriptome data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In accordance with the characteristics of gene expression, a type of T cells specifically expressing MKI67 was found and regarded as proliferative T cells ( Figure 8B ). Here we found that proliferation T cells infiltrating was a feature of the ccRCC immune microenvironment which was consistent with previously studies ( 20 22 , 70 ). Pseudo-time trajectory analysis on all T cells was performed in pRCC to further understand the proliferation characteristics of this cell type.…”
Section: Resultssupporting
confidence: 93%
“…In accordance with the characteristics of gene expression, a type of T cells specifically expressing MKI67 was found and regarded as proliferative T cells ( Figure 8B ). Here we found that proliferation T cells infiltrating was a feature of the ccRCC immune microenvironment which was consistent with previously studies ( 20 22 , 70 ). Pseudo-time trajectory analysis on all T cells was performed in pRCC to further understand the proliferation characteristics of this cell type.…”
Section: Resultssupporting
confidence: 93%
“…To further verify the relationship among ALDOB , ESRRG , and EFHD1 in ccRCC, single-cell RNA-seq data from GSE131685 and GSE171306 were employed ( 25 , 26 ). After quality control, a total of 34,371 cells from two ccRCC samples and three normal kidney samples were profiled ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…R package “Seurat” (version 4.0.2) was used to process the data ( 24 ). Three healthy kidney samples from GSE131685 ( 25 ) and two ccRCC samples from GSE171306 ( 26 ) were merged for further analysis. The single-cell RNA-seq data processing was described previously ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, scRNAseq, which is not limited by the determining markers, has dissected tumor heterogeneity in multiple types of human solid cancers [ 51 ]. In ccRCC, a few studies with scRNAseq have just begun to investigate immune cell heterogeneity, immune pathogenesis, and response to immunotherapy [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Analyzing tumor-infiltrating immune cells by scRNAseq, especially focusing on T cell exhaustion, suppressive TAMs, and inhibitory cell to cell interactions has shown to have clinical prognostic and predictive value regarding clinical outcomes and the response to immunotherapy.…”
Section: Single-cell Genomics To Study the Tumor Microenvironmentmentioning
confidence: 99%
“…Integrating various components of scRNAseq transcriptome into multi-omics measurements provides a better understanding of cell identity, fate, and function in the context of both normal biology and pathology [ 52 , 53 ]. The application of scRNAseq to renal parenchyma or kidney cancer is just at its inception and is helping provide a clearer understanding of cell of origin, tumor and immune cell heterogeneity, immune-suppressive microenvironment, therapeutic response, and ultimately prediction of prognosis [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%